The value of built heritage: Community, economy and environment - Irons, Janine; Armitage, L. (Pacific Rim Real Estate Society Conference, 2011)
Whilst legislatures at all levels of Australian government have been slower to establish heritage protection than many other OECD countries, the community’s commitment predates identifiable involvement by government in the conservation arena by more than two decades as illustrated by the foundation, in Sydney in the mid 1940’s, of the National Trust of Australia (AGPC 2006). It was not until the 1970’s that formal frameworks were established through statutory control mechanisms for the identification and protection of Australia’s rich stock of heritage places (Irons and Armitage 2010).Similarly, at the professional level, the relatively recent emergence and dissemination of standardised approaches to valuation and management practices for heritage property (e.g. IVSC 2007; API 2008;RICS 2009) across international boundaries is an acknowledgement of their special value and – to some extent – demonstrates a recognition of characteristics which are shared by diverse cultures (Armitage and Yau 2008).Set within the context of Australia’s commitment to the Kyoto protocols, requiring signatory countries to meet mandated reductions in the use of non-renewable resources, the potential opportunity cost savings achievable by the more effective use of existing built structures has re-emerged as an area of interest. The objective of this paper is to review the multifaceted elements which contribute to our perceptions of heritage reflecting values which incorporate yet transcend the merely economic (Ashworth 2002) within this contemporary perspective of the role of heritage property identified above. This paper draws upon a rigorous study (Irons 2008) which investigates in detail the effect of local heritage listing on the single family dwelling. The paper identifies the framework of heritage management in Australia and considers the many meanings of the relevant terminology. Concepts of cultural heritage, of place and of significance are discussed providing a preface to a review of the value of heritage from a number of perspectives. In an age of increased sensitivity to profligate resource consumption, this traditional view is then extended to consider the potential environmental benefits of heritage conservation, contributing a contemporary commentary to some economic, social and professional concerns and reflects upon the challenges of the journey yet to come.